Poultry Litter Compost and NPK fertilizers Induced Growth and Yield Performance of Boro Rice at Rooftop Farming (Journal of Biodiversity Conservation and Bioresource Management, 2024)
The effects of inorganic fertilizers and decomposed poultry litter on the growth and yield performance of boro rice (Oryza sativa L.) were assessed by conducting a pot experiment on the rooftop of a building in Charfasson town, Bhola. The experiment was laid out in a completely randomized design (CRD), having eight treatments with three replications each. Different agronomic parameters were measured at 30-day intervals after sowing of seeds and yield parameters after harvesting. The highest height (82.67 cm) at 90d, number of leaf (37.67) at 120d, longest leaf ( 39.67 cm) at 90d, and length of panicle (27.17 cm), number of grains/panicle (153.33), weight of grain/panicle (3.74 g), fresh weight of grains (62.35 g/pot), dry weight of grain (51.53 g/pot), dry weight of root (13.43 g/pot), rice yield (51.53 g/pot) or (5.67 t ha-1), highest B:C ratio (4.51), respectively, were found in the treatment T7: (3.0 t PL ha-1 + N100P25K90 kg ha-1). The results of treatments T7 and T8 are statistically identical. The overall best growth performance and yield of boro rice were achieved in T7: (3.0 t PL ha-1 + N100P25K90 kg ha-1) treatment on a rooftop farming system on the south coast of Bangladesh.Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 99-108